Fish ladders select fish traits on migration - still a growing problem for natural fish populations - Volpato, Gilson Luiz [UNESP]; Barreto, Rodrigo Egydio [UNESP]; Marcondes, Ana Lucia [UNESP]; Andrade Moreira, Paula Sueli [UNESP]; de Barros Ferreira, Magali Fatima [UNESP] (Taylor & Francis Ltd, 2009)
We investigated the potential selective effect of fish ladders on physiological and morphological profiles of the curimbata, Prochilodus lineatus, during reproductive migration in Brazil. We registered sex, body weight and length, plasma glucose, hepatosomatic and gonadosomatic indices (HSI and GSI, respectively), hematocrit, leucocrit, blood cell and nucleus areas, and the diameter of white and red muscle fibers in fish sampled at the bottom (downstream) and at the top (upstream) of a fish ladder at a hydroelectric dam. Males and females at the top of the ladder showed higher size (weight and length), white muscle fiber diameters, plasma glucose levels and lower hematocrit when compared with those at the bottom. These size and muscle traits assist fish to overcome the ladder barrier and bypass the dam, an effort that might be reflected in the glucose levels. Females also showed higher GSI at the top of the fish ladder, a trait possibly facilitating their reproduction upstream. These results indicate that a dam system favors fish with specific morphological-physiological profile. This may have a strong influence upon upstream fish populations over generations and implies the presence of artificial selective pressure.
Keywords: fish; migration; fish ladders; hydroelectric dams; artificial selection; Prochilodus lineatus